Digital clues of employment: A look at data processing from the marxian theory of alienated work. (Papeles, 2024)
The development of new forms of work based on technology makes it necessary to acknowledge digital clues of employment. In this essay, a return to the Marxian theory of alienated labor is proposed as the beginning of this development, applying the same concepts that Marx used for commodities to the treatment of data.
Keywords: Marx; alienation